Impact of Sea Pandan Leaf Fiber Volume Fraction on the Tensile Strength and Structural Morphology of Polypropylene Composites - Anugrah Budi Wicaksono; Lukas Felix Wibowo; Muhammad Ammar Nur Handyka (Aptek, 2025)
Natural fiber-reinforced polymer composites are increasingly developed due to their relatively low cost and environmental friendliness. This study aims to analyze the tensile strength and morphology of polypropylene composites reinforced with sea pandan leaf fibers. The reinforcing material used was sea pandan leaf fiber, while the matrix consisted of polypropylene plastic. The composite fabrication process employed the compression molding method at a temperature of 250Â°C for one hour. The fiber volume fractions used in this study were 20%, 25%, 30%, 35%, and 40%. The tensile test results indicated that the highest tensile strength, 25.82 MPa, occurred at a 35% fiber volume fraction, while the lowest strength, 10.34 MPa, was found at a 20% fraction. SEM observations revealed the presence of voids, cracks, fiber pull-outs, and impurities on the composite surface